Diagnosis and conservative therapy of retropharyngeal hematoma - Novriansyah, Wahyu Tri; Nukman, Novialdi (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACTBackground: Retropharyngeal hematoma is the accumulation of blood clots in the retropharyngeal space which can cause upper airway obstruction. Until now, controversy over surgical versus conservative therapy is still being debated. Purpose: Reporting one rare case of retropharyngeal hematoma. Case report: A 72-year-old man was brought to the emergency room with complaints of worsening dyspnea for 12 hours, after slipped and fell in the bathroom. Physical examination revealed purple discoloration on the posterior pharyngeal wall, CT scan showed inhomogeneous hyperdense masses, and coagulopathy. The patient underwent conservative therapy but finally died on the day-10 of treatment. Clinical question: How effective is the conservative therapy in retropharyngeal hematoma compared to surgical therapy? Review method: A literature search using keywords ”retropharyngeal hematoma” was conducted through Pubmed and Google Scholar. Result: Management of retropharyngeal hematoma is still controversial due to the lack of widely accepted guidelines. Conclusion: Conservative therapy in cases of retropharyngeal hematoma, should be administered aggressively, comprehensively, and with a strict protocol. ABSTRAKLatar belakang: Hematoma retrofaring adalah penumpukan bekuan darah di ruang retrofaring yang dapat menyebabkan obstruksi jalan nafas bagian atas. Hingga saat ini, kontroversi mengenai terapi bedah versus konservatif masih menjadi perdebatan. Tujuan: Melaporkan satu kasus hematoma retrofaring yang jarang terjadi. Laporan kasus: Seorang pria berusia 72 tahun dibawa ke ruang gawat darurat dengan keluhan sesak nafas yang semakin memburuk sejak 12 jam setelah jatuh karena terpeleset di kamar mandi. Pada pemeriksaan fisik didapatkan warna keunguan pada dinding posterior faring, CT scan terlihat massa hyperdense yang tidak homogen, serta koagulopati. Pasien menjalani terapi konservatif namun akhirnya meninggal pada hari ke-10 pengobatan. Pertanyaan klinis: Seberapa efektif terapi konservatif pada hematoma retrofaring dibandingkan dengan terapi bedah? Telaah literatur: Pencarian literatur menggunakan kata kunci ”retropharyngeal hematoma” dilakukan melalui Pubmed dan Google Scholar. Hasil: Penatalaksanaan hematoma retrofaring masih menjadi kontroversi karena belum adanya pedoman yang diterima secara luas. Kesimpulan: Terapi konservatif pada kasus hematoma retrofaring sebaiknya diberikan secara agresif, komprehensif, dan dengan protokol yang ketat.